A81 FUNCTIONAL ANALYSIS IMPLICATING SAMD9 MUTATION FOR INTESTINAL INFLAMMATION IN PATIENTS WITH MIRAGE SYNDROME AND INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Ishige, T; Guo, C; Warner, N; Pan, J; Hossain, K; Dhingani, N; Murchie, R; Muise, A
Abstract: Background: MIRAGE syndrome is caused by heterozygous mutation in the SAMD9 gene. The syndrome is characteristic of enteropathy, and is often fatal within the first 2 years of life. However, the pathogenesis of enteropathy in the syndrome is unknown. Aims: We present a case of MIRAGE syndrome (gestational age 35 weeks, birth weight 1330g) who developed restriction of growth, adrenal hypoplasia, genital anomaly, and enteropathy at the time of birth. Sigmoidoscopy showed longitudinal ulcers in rectum. Aim of this study is (1) to identify whether SAMD9 mutation is involved in early onset inflammatory bowel disease (IBD), and (2) to investigate the involvement of SAMD9 mutation in colitis. Methods: (1) Whole exome sequence (WES) results performed for IBD patients and their families in The Hospital for Sick Children were reviewed. Mucosal expression of SAMD9 in patients' biopsy samples were investigated by immunohistochemistry. (2) We assessed difference in TNF-alpha responsiveness between wild type (WT) or mutated (R1293W) SAMD9 using stably expressing HEK293 cell lines. Difference in apoptosis were measured using western blotting and Caspase assays. Results: (1) Among our WES data, 3 patients from 2 families (2 ulcerative colitis, 1 colonic Crohn's disease) had mutation in SAMD9 gene. Biopsy samples from IBD patients showed increased SAMD9 signals by immunohistochemistry, whereas those from MIRAGE syndrome patient and these 3 patients showed decreased signals. (2) R1293W expressing cells showed increased expression of cleaved Poly ADP-ribose polymerase (PARP) when compared with WT and control. X-Linked inhibitor of apoptosis (XIAP), a known apoptosis inhibitor involves in early onset IBD, were decreased in R1293W mutations. Caspase assay showed increased caspase 3/7 activity in mutated cell lines. Apoptosis was also observed in pathology of the patient's intestinal mucosal biopsy specimen. Conclusions: SAMD9 might be a novel gene associated with development of pediatric IBD. Suppression of XIAP might result in increased apoptosis and intestinal inflammation observed in patients with SAMD9 mutation. Funding Agencies: None